2014
DOI: 10.1080/13527258.2013.842607
|View full text |Cite
|
Sign up to set email alerts
|

Digital heritage in a Melanesian context: authenticity, integrity and ancestrality from the other side of the digital divide

Abstract: This article examines how digital heritage, in the form of 3D digital objects, fits into particular discourses around identity, ancestrality and cultural transmission in Melanesia. Through an ethnographic analysis of digital heritage use amongst the Nalik community in New Ireland (Papua New Guinea), it demonstrates how digital heritage is understood not in terms of deceit and a loss of authenticity, but instead, towards an understanding of authenticity in terms of completeness and integrity. A notion of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The field of digital heritage started to take shape in the 1990s but has expanded more substantially in the last ten years, focussing especially on the roles and impact of digital technologies in museum and gallery contexts (for foundational work on the topic, see Fahy 1995;Anderson 1997;Arvanitis 2002;Galani and Chalmers 2002;Parry 2007aParry , 2007bParry , 2010Cameron and Kenderdine 2010). Since then, published material in this area has been concerned primarily with digital engagement with the past or the digitisation of analogue resources (see all the citations given above and, more recently, Kidd 2011;Geismar 2012;Ridge 2014;Were 2015;King, Stark and Cooke 2016;Díaz-Andreu 2017;Jones et al 2017), whereas literature dealing specifically with digitally-born and digitally-enabled research remains very limited. Moreover, the few existing studies of this kind tend to take one of two directions.…”
Section: Aimsmentioning
confidence: 99%
“…The field of digital heritage started to take shape in the 1990s but has expanded more substantially in the last ten years, focussing especially on the roles and impact of digital technologies in museum and gallery contexts (for foundational work on the topic, see Fahy 1995;Anderson 1997;Arvanitis 2002;Galani and Chalmers 2002;Parry 2007aParry , 2007bParry , 2010Cameron and Kenderdine 2010). Since then, published material in this area has been concerned primarily with digital engagement with the past or the digitisation of analogue resources (see all the citations given above and, more recently, Kidd 2011;Geismar 2012;Ridge 2014;Were 2015;King, Stark and Cooke 2016;Díaz-Andreu 2017;Jones et al 2017), whereas literature dealing specifically with digitally-born and digitally-enabled research remains very limited. Moreover, the few existing studies of this kind tend to take one of two directions.…”
Section: Aimsmentioning
confidence: 99%
“…It should be noted that all these arguments are purely doctrinal and not based on data regarding how affected communities perceive digital restitution of their historical and religious treasures. In this particular field, lawyers tend to neglect the evidence-based approach, although there is research on the subject done by anthropologists; for instance, for the Melanesian community [20].…”
Section: Nfts and Property Lawsmentioning
confidence: 99%
“…A recent survey [31] that focused on the user ability of a more educated cohort (94% Ph.D. or Master's degree; 6% Bachelor's degree or undergraduate) in 28 countries worldwide showed that even this group had serious concerns regarding the utility, safety, accessibility, and efficiency of "smart" services. The digital divide, particularly in the Global South and for the elderly, is of concern [32][33][34][35][36] and must be considered using an inclusionary and participatory approach [37][38][39]. It seems, then, that community consultation (or participatory planning, or what we term here "familiarity" with community) should be incorporated as an important element of Smart City planning (or the bottom-up approach, as noted above), with Allahar [24] concluding that "The success of building smart cities has been traced by some scholars to depth of community engagement and level of citizen participation".…”
Section: What Is a Smart City?mentioning
confidence: 99%